1997
DOI: 10.1577/1548-8675(1997)017<0314:eoefoc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrofishing Fields on Captive Juveniles of Two Endangered Cyprinids

Abstract: We conducted laboratory experiments to address concerns about potential harmful effects of electrofishing on juvenile humpback chubs Gila cypha. Four types of square‐wave pulsed DC in homogeneous fields were tested: 30 Hz (12% duty cycle), 60 Hz (24% duty cycle), 80 Hz (40% duty cycle), and a complex pulse train of three 240‐Hz, 2.6‐ms pulses delivered at 15 Hz (12% duty cycle). We first determined peak‐voltage gradients for each current sufficient to induce the electroshock responses of taxis, narcosis, or te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 6 publications
2
17
0
1
Order By: Relevance
“…Lack of vertebral damage in our study was consistent with results from other studies on small cyprinids (Cape Fear shiner: Holliman et al 2003; juvenile humpback chub Gila cypha and bonytail G. elegans: Ruppert and Muth 1997). Electroshock can induce hemorrhage associated with the vertebral column in small fish (Ruppert and Muth 1997;Cooke et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Lack of vertebral damage in our study was consistent with results from other studies on small cyprinids (Cape Fear shiner: Holliman et al 2003; juvenile humpback chub Gila cypha and bonytail G. elegans: Ruppert and Muth 1997). Electroshock can induce hemorrhage associated with the vertebral column in small fish (Ruppert and Muth 1997;Cooke et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…No delayed mortality occurred for channel catfish observed for 5 d after exposure, even though 68% had died during the first hour after electroshocking. Previous studies reported low rates of delayed mortality (Ͻ10%) for other species (Hudy 1985;Barrett and Grossman 1988;Schneider 1992;McMichael 1993;Habera et al 1996;Ruppert and Muth 1997;Cooke et al 1998), although previous studies did not consider the developmental stages we found to be the most sensitive to the lethal effects of electroshocking.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, neither single nor multiple exposures to DC electrofishing had significant effects on survival of mottled sculpin Cottus bairdi over a 30-d period (Barrett and Grossman 1988). Survival of humpback chub Gila cypha and bonytails G. elegans, endangered cyprinids, was not affected by electroshock though there was evidence of broken blood vessels along the spinal column in some bonytails (Ruppert and Muth 1997). Cooke et al (1998) found that electrofishing induced little mortality (4-9%) in greenside darters E. blennoides and noted broken blood vessels and vertebral damage in some fish.…”
Section: Discussionmentioning
confidence: 96%
“…Based on prior studies on small fish, we identified electrical waveform, pulse frequency, voltage gradient, electroshock duration, and fish length as potential risk factors for mortality of electroshocked Cape Fear shiners. Whether these variables influence injury in small fish is not known, but injury to Cape Fear shiners was a concern because electroshock-induced injury has been reported in fish about 40-100 mm long (Ruppert and Muth 1997;Cooke et al 1998).…”
mentioning
confidence: 99%